2019
DOI: 10.1371/journal.pone.0212123
|View full text |Cite
|
Sign up to set email alerts
|

Gamma radiation induces locus specific changes to histone modification enrichment in zebrafish and Atlantic salmon

Abstract: Ionizing radiation is a recognized genotoxic agent, however, little is known about the role of the functional form of DNA in these processes. Post translational modifications on histone proteins control the organization of chromatin and hence control transcriptional responses that ultimately affect the phenotype. The purpose of this study was to investigate effects on chromatin caused by ionizing radiation in fish. Direct exposure of zebrafish (Danio rerio) embryos to gamma radiation (10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 53 publications
2
13
0
Order By: Relevance
“…offspring, but interestingly these effects were diminished in F2 offspring (Lindeman et al 2019, submitted). Although only exposed embryo's were analysed similar changes in histone markes were found for Atlantic salmon (Salmo salar) at higher dose rates (Lindeman et al 2019).…”
Section: Evidence For a Role Of Epigenetics In Long-mentioning
confidence: 57%
See 1 more Smart Citation
“…offspring, but interestingly these effects were diminished in F2 offspring (Lindeman et al 2019, submitted). Although only exposed embryo's were analysed similar changes in histone markes were found for Atlantic salmon (Salmo salar) at higher dose rates (Lindeman et al 2019).…”
Section: Evidence For a Role Of Epigenetics In Long-mentioning
confidence: 57%
“…These methylation changes could be linked to changes in gene pathways and adverse effects found in progeny (Hurem et al 2017;Hurem et al 2018b). In the same exposure study, miRNA expression was measured in first filial offspring and histone marks H3K4me3, H3K9me4 and H3K27me3 at 3 specific loci (Lindeman et al 2019). There were 23 differentially expressed miRNAs indicating a multifaceted response to ionising radiation exposure (Martin et al 2019, in preparation).…”
Section: Evidence For a Role Of Epigenetics In Long-mentioning
confidence: 99%
“…These observations suggest that cell cycle checkpoints are a key factor for preserving genome integrity. Lindelman et al [11] reported that exposing zebrafish embryos to radiation for 3 h beginning at 2.5 hpf (256-cell stage) induced locus-specific changes in the enrichment of histone modifications. Similar results were observed when Atlantic salmon embryos were exposed to radiation from the 1-cell stage to the early gastrula stage [11].…”
Section: Genome Integritymentioning
confidence: 99%
“…Lindelman et al [11] reported that exposing zebrafish embryos to radiation for 3 h beginning at 2.5 hpf (256-cell stage) induced locus-specific changes in the enrichment of histone modifications. Similar results were observed when Atlantic salmon embryos were exposed to radiation from the 1-cell stage to the early gastrula stage [11]. To assess whether this change affects chromatin structure or organization, additional experiments must be carried out.…”
Section: Genome Integritymentioning
confidence: 99%
See 1 more Smart Citation